1996
DOI: 10.1097/00000478-199600001-00003
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal and Diffuse Gastric Cancers Arise in a Different Background of Helicobacter pylori Gastritis Through Different Gene Involvement

Abstract: Investigation of extensively sampled nontumor gastric mucosa from 205 early gastric cancers showed Helicobacter pylori colonization in 85% of cases, including 100% of diffuse and 78% (83% in 97 cases with Swiss rolls) of glandular or mixed cancers. Intestinal metaplasia, including its type III variant, was prominent in the mucosa associated with glandular and mixed (but not diffuse) early cancers. Both glandular (usually called "intestinal") and diffuse-type cancers showed admixtures of intestinal and gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
2
8

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 46 publications
9
77
2
8
Order By: Relevance
“…But since the peri-tumour zone of most diffuse cancers lack these long-lasting intermediate steps, the importance of a preceding H. pylori infection in this subtype may be questioned. It has been suggested that H. pylori-induced chronic gastritis, involving an active renewal of gastric epithelium sensitive to oxidative carcinogenes, could be an early common starting-point in the genesis of both histologic types (Solcia et al, 1996). If genes primarily responsible for cell proliferation and differentiation are damaged, intestinal type cancer may then develop via the intermediate steps outlined above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But since the peri-tumour zone of most diffuse cancers lack these long-lasting intermediate steps, the importance of a preceding H. pylori infection in this subtype may be questioned. It has been suggested that H. pylori-induced chronic gastritis, involving an active renewal of gastric epithelium sensitive to oxidative carcinogenes, could be an early common starting-point in the genesis of both histologic types (Solcia et al, 1996). If genes primarily responsible for cell proliferation and differentiation are damaged, intestinal type cancer may then develop via the intermediate steps outlined above.…”
Section: Discussionmentioning
confidence: 99%
“…If genes primarily responsible for cell proliferation and differentiation are damaged, intestinal type cancer may then develop via the intermediate steps outlined above. Alternatively, if the early H. pylori-activated carcinogenic process affects genes involved in cell adhesion and basal membrane integrity, the secretory mucosal function would be retained (signet-ring cells), while prerequisites are formed for the invasiveness characterizing diffuse adenocarcinomas (Solcia et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, for gastric cancer to coexist with duodenal ulcer, an unrelated cause of mucosal atrophy must play some part, and the diffuse type of gastric cancer may be predominant in such cases [6,93,99].…”
Section: Failure To Notice Lesionsmentioning
confidence: 99%
“…The most frequent gastric malignancy is the intestinal type, which is often preceded by sequential steps of precancerous changes, including atrophic gastritis, intestinal metaplasia, and either dysplasia or adenoma. In contrast, the diffuse type of gastric carcinoma tends to arise de novo and is infrequently associated with dysplasia or adenoma [66][67][68][69]. The sequential accumulation of alternations of APC and K-ras genes, characteristic of the colorectal adenoma-carcinoma sequence, however, does not occur frequently between adenoma and intestinal type adenocarcinoma of the stomach [27,[70][71][72][73][74][75][76][77].…”
Section: Epigenetic Alterations In Early Gastric Tumorigenesismentioning
confidence: 99%